Bronchiectasis in Primary Antibody Deficiencies: A Multidisciplinary Approach - Wall, Luke A.; Wisner, Elizabeth L.; Gipson, Kevin S.; Sorensen, Ricardo U. (Frontiers in Immunology, 2020)
Bronchiectasis, the presence of bronchial wall thickening with airway dilatation, is a particularly challenging complication of primary antibody deficiencies. While susceptibility to infections may be the primary factor leading to the development of bronchiectasis in these patients, the condition may develop in the absence of known infections. Once bronchiectasis is present, the lungs are subject to a progressive cycle involving both infectious and non-infectious factors. If bronchiectasis is not identified or not managed appropriately, the cycle proceeds unchecked and yields advanced and permanent lung damage. Severe symptoms may limit exercise tolerance, require frequent hospitalizations, profoundly impair quality of life and lead to early death. This review article focuses on the appropriate identification and management of bronchiectasis in patients with primary antibody deficiencies. The underlying immune deficiency and the bronchiectasis need to be treated from combined immunology and pulmonary perspectives, reflected in this review by experts from both fields. An aggressive multidisciplinary approach may reduce exacerbations and slow the progression of permanent lung damage.